In-vitro evaluation of multicomponent scaffold with kappa carrageenan, tendon extracellular matrix and calcium-magnesium silicate for periodontal bone regeneration - Supraja G.; S. Balaji Ganesh; Raja Kumar; Gurumoorthy Kaarthikeyan (Journal of Oral Biology and Craniofacial Research)
Introduction: Chronic periodontitis is a complex combinatory disease that eventually upsets periodontal tissues, ultimately leading to tooth loss. In vertical bone loss defects, therapy includes surgical procedures, such as flap surgery with debridement associated with scaffolds, grafts, or membranes. The aim of the study is to fabricate a novel carrageenan, Calcium Magnesium Silicate (CaMgSiO), and ovine extracellular matrix (ECM)-based scaffold for periodontal bone regeneration. Materials and methods: To a 2 % carrageenan solution, 1 mg/mL of CaMgSiO and ECM was added. This homogenous solution was immersed in 0.15 M CaCl2 solution. The divalent cations (Ca+ 2 ions) were diffused into the gel and crosslinked to form a scaffold. The cross-linked scaffold (kappa carrageenan-CaMgSiO-ECM) was washed twice, underwent lyophilization and stored at 4 °C for further use. Scaffold characterization was done by means of X-ray diffraction (XRD), Raman spectrum, and scanning electron microscope (SEM), and energy dispersive spectroscopy (EDS). Then hemocompatibility assay, swelling analysis, and differentiation test were done to assess the biocompatibility of the scaffold. Result: Calcium was observed with a weight percentage of 16.7 %, silicate with 27.6 wt%, and magnesium with 2.8 wt% via EDS spectra. Kappa carrageenan, CaMgSiO + ECM scaffold has good agreement with red blood cells with a minimal lysis of 2 % at the concentration of 10 mg/mL, and the differentiation test showed maximum proliferation of cells. Conclusion: The novel CaMgSiO ECM scaffold significantly enhances cell proliferation; it is highly hemocompatible and has enhanced mineralization properties. Hence, incorporation of bioactive bioceramics induces stability as well as enhances the regeneration properties of the tendon-derived ECM.